(untitled) (Studia Iberystyczne, 2019)
Patriarchy and Madness in the Brazilian Novel A comparative study of the novels Fogo Morto, by José Lins do Rego (1943); A menina morta, by Cornélio Penna (1954) and Crônica da casa assassinada, by Lúcio Cardoso (1959) allows a glimpse into a complex framework of relations between novelistic form and Brazilian society. They are novels whose plots take place in the interior or in the shadow of the domestic space whose meaning points to the specificities of Brazilian society anchored in the structure and functioning of the slave production mode, expressed by the significant presence of the home as casa-grande. Thus, through the bias of introspective prose, the novels capture the relation between the sphere of the family and the formation of the subject, approaching patriarchy to the traces of madness.